2021
DOI: 10.1177/1351010x21993742
|View full text |Cite
|
Sign up to set email alerts
|

Case study: A survey of perceived noise in Canadian multi-unit residential buildings to study long-term implications for widespread teleworking

Abstract: Trends of urbanization, densification, and telework all point to increasing exposure to ambient noise for workers. With the lockdown policies implemented in response to COVID-19, a research opportunity to study perceived noise exposure for teleworking arose. This paper presents the results of a survey on noise issues in multi-unit residential buildings (MURBs) and the consequent effects on occupants' well-being and productivity during the lockdown. Responses were collected from 471 MURB occupants across Canada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…They reported that neighbour noise was more annoying than outdoor noises during the lockdown, suggesting that this type of noise source is more problematic than other typical sources of community noise, when considered in the context of an enforced “stay home” policy. This brought other researchers to question what the positive role of indoor soundscape could be to promote well-being in times of social distancing ( Andargie et al, 2021 ; Dzhambov et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that neighbour noise was more annoying than outdoor noises during the lockdown, suggesting that this type of noise source is more problematic than other typical sources of community noise, when considered in the context of an enforced “stay home” policy. This brought other researchers to question what the positive role of indoor soundscape could be to promote well-being in times of social distancing ( Andargie et al, 2021 ; Dzhambov et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing part of the literature has dealt so far with the effects of the environmental conditions on building occupants' health, mental health and quality of life, [1][2][3] and several studies have specifically focused on the quality of the domestic environment for building occupants' during the COVID-19 lockdown. [4][5][6] Industry and research are debating on the design and operation of buildings [7][8][9] in the light of the new home uses (e.g. working from home, WFH) and the need to control the spread of the virus (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was found that people living in multi-unit residential buildings across Canada experienced a somewhat increased annoyance due to the vehicular noise despite a general decrease in ambient levels during the lockdown. 20 For a quiet residential area in Japan, the survey suggested that the participants perceived the noise levels to be the same during the lockdown and a few weeks after the restrictions were eased. 21 A survey of over 1000 participants across Turkey revealed that annoyance due to outdoor noise reduced considerably during the lockdown, particularly for busy residential neighborhoods, and it positively correlated with stress and anxiety levels.…”
Section: Introductionmentioning
confidence: 99%